Assessment of knowledge regarding prescription of drugs among BDS interns - Surekha Rathod; Ishita Roy; Pranjali V Bawankar; Krutika Deshmukh; Vaishnavi K Gadbail (Wolters Kluwer Medknow Publications, 2020)
Background: Interns are the future professionals who would be treating patients on their own once they graduate, so it is mandatory that they be aware of correct prescribing. The present study aimed to assess the knowledge of dental interns regarding the prescription of drugs. Methodology: A structured, self-administered questionnaire was designed and given to 68 interns. The data were collected and analyzed using SPSS version 21. Results: A statistically significant number of interns were aware of the prescription of drugs for dental patients. However, it is essential for every intern to have sound knowledge regarding the pharmacodynamics, dosage, and prescription of drugs for dental infections in healthy as well as systemically compromised patients. Conclusion: A majority of interns had moderate knowledge regarding drug prescription, and special efforts are required to educate the interns for the same.